Endoscopic anatomy of the approaches to the sellar area and planum sphenoidale - Henrique Faria Ramos; Tatiana Alves Monteiro; Carlos Diógenes Pinheiro Neto; Pedro Paulo Mariani; Felipe Sartor Guimarães Fortes; Luiz Ubirajara Sennes (Arquivos de Neuro-Psiquiatria)
The productive work between otolaryngologists and neurosurgeons has resulted in the emergence of endoscopic endonasal skull base surgery. The goal of the present study is to describe the endoscopic anatomy of the endonasal approach to the sellar region and planum sphenoidale, highlighting the key points of the surgical approach and the neurovascular landmarks. METHOD: Descriptive study of the endoscopic endonasal dissection of 9 fresh cadavers with exposure of the anatomic structures. RESULTS: The endoscopic endonasal ethmoidectomy and sphenoidotomy allows an expanded access to the sellar area and planum sphenoidale. The surface anatomy of the sphenoid sinus is easily identifiable and provides safe landmarks, guiding the intracranial dissection. CONCLUSION: The endoscopic endonasal approach to the skull base by the ENT and neurosurgeon is feasible, but it requires adequate anatomical knowledge and endoscopic skills for its realization, which can be obtained by practicing in cadavers.